Identification of Critical Land Using GIS for Flood Control Efforts in Bireuen Regency: Identifikasi Lahan Kritis Berbasis SIG Dalam Upaya Pengendalian Banjir di Kabupaten Bireuen - Cut Ayu Lizar; Halus Satriawan; Cut Azizah; Maysa Fitri (Media Ilmiah Teknik Lingkungan (MITL), 2026)
Flooding is an environmental problem that frequently occurs in Bireuen Regency and is influenced by physical land conditions and land degradation. Changes in land use, slope, land function, and erosion hazard levels can reduce the hydrological function of land and increase surface runoff. This study aims to identify and map land criticality using a Geographic Information System (GIS) as a supporting effort for flood control in Bireuen Regency. The research method was conducted through spatial analysis using an overlay technique of several parameters causing land criticality, including land cover, slope, land function, and erosion hazard level. The results show that Bireuen Regency is classified into five levels of land criticality: non-critical, potentially critical, moderately critical, critical, and very critical. Moderately critical land dominates the study area, covering 71,399.60 ha. Non-critical and potentially critical lands cover 44,275.03 ha and 36,130.94 ha, respectively. Meanwhile, critical and very critical lands cover 24,686.63 ha and 2,639.78 ha, generally distributed in areas with steep slopes and high erosion hazard levels. The identification of critical land is expected to serve as a basis for prioritizing land rehabilitation and flood control planning in Bireuen Regency.Flooding is an environmental problem that frequently occurs in Bireuen Regency and is influenced by physical land conditions and land degradation. Changes in land use, slope, land function, and erosion hazard levels can reduce the hydrological function of land and increase surface runoff. This study aims to identify and map land criticality using a Geographic Information System (GIS) as a supporting effort for flood control in Bireuen Regency. The research method was conducted through spatial analysis using an overlay technique of several parameters causing land criticality, including land cover, slope, land function, and erosion hazard level. The results show that Bireuen Regency is classified into five levels of land criticality: non-critical, potentially critical, moderately critical, critical, and very critical. Moderately critical land dominates the study area, covering 71,399.60 ha. Non-critical and potentially critical lands cover 44,275.03 ha and 36,130.94 ha, respectively. Meanwhile, critical and very critical lands cover 24,686.63 ha and 2,639.78 ha, generally distributed in areas with steep slopes and high erosion hazard levels. The identification of critical land is expected to serve as a basis for prioritizing land rehabilitation and flood control planning in Bireuen Regency.